Game “Wayang Fighter” pada Platform Android menggunakan Algoritma Basic Probability - Muliawan, Nyoman Adi; Wiranatha, A.A.K. Agung Cahyawan; Wibawa, Kadek Suar (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.3 Desember 2015DO - 10.24843/LKJITI.2015.v06.i03.p06, 2015)
Culture is a habit which contains important values ??and fundamentals that are passed from generation to generation. Puppet is one of Indonesian culture defined by UNESCO as world heritage on 7 November 2003. Game Wayang Fighter is a fighting game was adapted from story of Mahabharata. Game created by applying the Basic Probability Algorithm, which is an algorithm that assesses all the possibilities that computers do, before the player taking a decision. Game Wayang Fighter built using Corona SDK with Lua Programming Language that was applied to the Android Smartphone. The results obtained by questionnaire for this game is 66% of users said their knowledge of the story of Mahabharata increase and 55% of users say interested in Puppet Culture.